Functional characterization of a gamma-glutamyl phosphate reductase ProA in proline biosynthesis and promoting expression of type three secretion system in Ralstonia solanacearum - Guan, Yue; Wang, Rongsheng; Chen, Nan; Zhu, Yalan; Han, Liangliang; Chen, Xinping; Li, Jing; Zhang, Yong (Frontiers in Microbiology, 2022)
Ralstonia solanacearum RSc2741 is annotated as a gamma-glutamyl phosphate reductase ProA that catalyzes the second reaction to form proline from glutamate. Here, we experimentally demonstrated that proA mutants were proline auxotroph that failed to grow in a minimal medium. Supplementary proline, but not glutamate fully restored the diminished growth, confirming that ProA is responsible for biosynthesis of proline from glutamate in R. solanacearum. ProA was previously screened as one of candidates regulating expression of genes for type three secretion system (T3SS) that is essential for pathogenicity of R. solanacearum. Here, ProA was confirmed to be important for expression of the T3SS both in vitro and in planta via pathway of PrhG-HrpB, and its involvement on the T3SS was independent of growth deficiency under nutrient limited conditions. The proA mutant grew normally in intercellular spaces of tobacco leaves, while its abilities to invade and colonize host xylem vessels were substantially impaired, which was about one-day delay for proA mutants to invaded xylem vessels and about one order of magnitude less than the wild-type strain to proliferate to the maximum cell densities in xylem vessels. It thus resulted in substantially impaired virulence of proA mutants toward host tobacco plants. All taken together, these results extend our insights into understanding of biological function of ProA and sophisticated regulation on the T3SS and pathogenicity in R. solanacearum.